C3a Enhances the Formation of Intestinal Organoids through C3aR1 - Matsumoto, Naoya; Satyam, Abhigyan; Geha, Mayya; Lapchak, Peter H.; Dalle Lucca, Jurandir J.; Tsokos, Maria G.; Tsokos, George C. (Frontiers in Immunology, 2017)
C3a is important in the regulation of the immune response as well as in the development of organ inflammation and injury. Further, C3a contributes to liver regeneration but its role in intestinal stem cell function has not been studied. We hypothesized that C3a is important for intestinal repair and regeneration. Intestinal organoid formation, a measure of stem cell capacity, was significantly limited in C3-deficient and C3a receptor (C3aR) 1-deficient mice while C3a promoted the growth of organoids from normal mice by supporting Wnt-signaling but not from C3aR1-deficient mice. Similarly, the presence of C3a in media enhanced the expression of the intestinal stem cell marker Lgr5 and of the cell proliferation marker Ki67 in organoids formed from C3-deficient but not from C3aR1-deficient mice. Using Lgr5.egfp mice we showed significant expression of C3 in Lgr5+ intestinal stem cells whereas C3aR1 was expressed on the surface of various intestinal cells. C3 and C3aR1 expression was induced in intestinal crypts in response to ischemia/reperfusion injury. Finally, C3aR1-deficient mice displayed ischemia/reperfusion injury comparable to control mice. These data suggest that C3a through interaction with C3aR1 enhances stem cell expansion and organoid formation and as such may have a role in intestinal regeneration.